Detection of SARS-CoV-2 virus using an alternative molecular method and evaluation of biochemical, hematological, inflammatory, and oxidative stress in healthcare professionals. (September 2021) - Trassante, Carla Marcelino; Barboza, Victor dos Santos; Rocha, Liziane dos Santos; Correa, Paulo Maximiliano; Luchese, Cristiane; Wilhelm, Ethel Antunes; Pereira de Pereira, Claudio Martin; Baldissera, Matheus Dellaméa; Rech, Virginia Cielo; Giongo, Janice Luehring; de Almeida Vaucher, Rodrigo
Abstract: In early December 2019, an outbreak of coronavirus disease 2019 caused by a new strain of coronavirus (SARS-CoV-2), occurred in the city of Wuhan, Hubei Province, China. On January 30, 2020, the World Health Organization (WHO) declared the outbreak a public health emergency of international concern. Since then, frontline healthcare professionals have been experiencing extremely stressful situations and damage to their physical and mental health. These adverse conditions cause stress and biochemical, hematological, and inflammatory changes, as well as oxidative damage, and could be potentially detrimental to the health of the individual. The study population consisted of frontline health professionals working in BHU in a city in southern Brazil. Among the 45 participants, two were infected with the SARS-CoV-2 virus and were diagnosed using immunochromatographic tests such as salivary RT-LAMP and qRT-PCR. We also evaluated biochemical, hematological, inflammatory, and oxidative stress markers in the participants. The infected professionals (CoV-2-Prof) showed a significant increase in the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), cholesterol, lactic dehydrogenase, lymphocytes, and monocytes. In this group, the levels of uric acid, triglycerides, leukocytes, neutrophils, hemoglobin, hematocrit, and platelets decreased. In the group of uninfected professionals (NoCoV-2-Prof), significant increase in HDL levels and the percentages of eosinophils and monocytes, was observed. Further, in this group, uric acid, LDH, triglyceride, and cholesterol levels, and the hematocrit count and mean corpuscular volume were significantly reduced. Both groups showed significant inflammatory activity with changes in the levels of C-reactive protein and mucoprotein. The NoCoV-2-Prof group showed significantly elevated plasma cortisol levels. To our kowledge, this study is the first to report the use of the RT-LAMP method with the saliva samples of health professionals, to evalute of SARS-CoV-2. Highlights: RT-LAMP assay can detect SARS-CoV-2 in the saliva of healthcare professionals. Healthcare professionals faced stressful situations during the pandemic. Biochemical, hematological and inflammatory changes are evident in these individuals. Oxidative damage is also observed, potentially damaging workers.